Quantitative powder diffraction using a (2 + 3) surface diffractometer and an area detector. Issue 4 (16th July 2021) - Abbondanza, Giuseppe; Larsson, Alfred; Carlá, Francesco; Lundgren, Edvin; Harlow, Gary S.
Abstract : Conversion of 2D detector images measured on a (2 + 3) surface diffractometer to meaningful intensities that can be used for quantitative analysis of powdered and textured materials is discussed. Abstract : X‐ray diffractometers primarily designed for surface X‐ray diffraction are often used to measure the diffraction from powders, textured materials and fiber‐texture samples in 2gθ scans. Unlike in high‐energy powder diffraction, only a fraction of the powder rings is typically measured, and the data consist of many detector images across the 2gθ range. Such diffractometers typically scan in directions not possible on a conventional laboratory diffractometer, which gives enhanced control of the scattering vector relative to the sample orientation. There are, however, very few examples where the measured intensity is directly used, such as for profile/Rietveld refinement, as is common with other powder diffraction data. Although the underlying physics is known, converting the data is time consuming and the appropriate corrections are dispersed across several publications, often not with powder diffraction in mind. This paper presents the angle calculations and correction factors required to calculate meaningful intensities for 2gθ scans with a (2 + 3)‐type diffractometer and an area detector. Some of the limitations with respect to texture, refraction and instrumental resolution are also discussed, as is the kind of information that one can hope to obtain.